Clinical Value of Complex Echocardiographic Left Ventricular Hypertrophy Classification Based on Concentricity, Mass, and Volume Quantification - Barbieri, Andrea; Albini, Alessandro; Maisano, Anna; De Mitri, Gerardo; Camaioni, Giovanni; Bonini, Niccolò; Mantovani, Francesca; Boriani, Giuseppe (Frontiers in Cardiovascular Medicine, 2021)
Echocardiography is the most validated, non-invasive and used approach to assess left ventricular hypertrophy (LVH). Alternative methods, specifically magnetic resonance imaging, provide high cost and practical challenges in large scale clinical application. To include a wide range of physiological and pathological conditions, LVH should be considered in conjunction with the LV remodeling assessment. The universally known 2-group classification of LVH only considers the estimation of LV mass and relative wall thickness (RWT) to be classifying variables. However, knowledge of the 2-group patterns provides particularly limited incremental prognostic information beyond LVH. Conversely, LV enlargement conveys independent prognostic utility beyond LV mass for incident heart failure. Therefore, a 4-group LVH subdivision based on LV mass, LV volume, and RWT has been recently suggested. This novel LVH classification is characterized by distinct differences in cardiac function, allowing clinicians to distinguish between different LV hemodynamic stress adaptations in various cardiovascular diseases. The new 4-group LVH classification has the advantage of optimizing the LVH diagnostic approach and the potential to improve the identification of maladaptive responses that warrant targeted therapy. In this review, we summarize the current knowledge on clinical value of this refinement of the LVH classification, emphasizing the role of echocardiography in applying contemporary proposed indexation methods and partition values.